Isolation and characterization of keratinophilic fungi and related dermatophytes from various public parks of Jaipur, India (Funded Research Article) - SUBHASH GORA; MAMATA GORA; NEETU JAIN; SHAMSHAD UL HAQ; MEENAKSHI SHARMA; SUNITA MAHARIYA (International Journal of Pharma and Bio Sciences, 2017)
Keratinophilic fungi and related dermatophytes are important both economically as well as naturally because they play an important role in degradation of keratin material present in soil, which is due to human and animal presence. They grow mostly on keratin protein’s decomposition product, obtained from decomposition of hair, nails, horns, claws etc. Present study characterized soil samples from 20 public parks of Jaipur district, India for occurrence of keratinophilic fungi. A total of 15 species belonging to 5 genera were isolated and identified from 125 soil samples. 79 soil samples were found positive, from which 144 isolates of keratinophilic fungal were recovered. Chrysosporium tropicum being the most prevailing of all with 22 isolates and present in 12 public parks out of 20 (60 %), followed by C. indicum and Trichophyton mentagrophytes. Epidermophyton was least spread of all, present only in 4 parks, out of 20 public parks. In many positive samples more than 2 isolates were obtained. Microsporum canis prevalence in public parks is the finding of this study which is due to roaming of rouge animals.